Screen Adaptation of The Animated Film Asal Usul Banyuwangi on Youtube Based on Eneste’s Concept: Narrative Transformation and Cultural Values in Digital Children’s Literature - Inno Cahyaning Tyas; Rusdhianti Wuryaningrum (Tabasa: Jurnal Bahasa, Sastra Indonesia, dan Pengajarannya, 2026)
Changes in story structures and representations of cultural values can be seen with digital adaptations of folklore into animated YouTube films. This research seeks to understand the cultural values and processes of screen adaptations of the animated story Asal Usul Banyuwangi (The Origin of Banyuwangi) using the concept of screen adaptation by Eneste. Using a qualitative descriptive approach, data was collected from 7 YouTube channels that adapt the story. Using the interactive model of Miles and Huberman, the authors analyzed the plot, characterization, conflict, dialogue, and cultural elements. The authors validated the findings by consulting with a cultural expert from Banyuwangi. The authors conclude that Reduction is the primary strategy for simplifying the episodic structure of Lontar Sri Tanjung, while Addition and Varied Modification occur in a more selective manner. Bug D'Art Studio is the closest channel to the original text structure and presents deviations while still preserving the essence of the story. Despite the changes in structure, the values of culture, loyalty, responsibility, and local identity still exist and are communicated in a manner more understandable for the children. The authors therefore conclude that cultural and narrative negotiations that allow the folklore to thrive in digital children’s literature are processes that can be seen in the screen adaptations of YouTube animations. Cerita rakyat yang diadaptasi ke dalam animasi digital di Youtube mengalami perubahan dalam struktur cerita dan representasi nilai-nilai budaya. Studi ini bertujuan untuk meneliti proses adaptasi layar dan nilai-nilai budaya yang terdapat dalam film animasi Asal Usul Banyuwangi, berdasarkan konsep adaptasi layar Eneste. Pendekatan kualitatif deskriptif digunakan, dengan data diambil dari tujuh saluran Youtube yang mengadaptasi cerita tersebut. Elemen naratif seperti plot, karakter, konflik, dialog, dan simbol budaya dianalisis menggunakan model interaktif Miles dan Huberman. Temuan diverifikasi melalui konsultasi dengan pakar budaya Banyuwangi. Studi ini menunjukkan bahwa reduksi menjadi strategi utama dalam menyederhanakan struktur episodik Lontar Sri Tanjung, sementara penambahan dan modifikasi beragam muncul secara selektif. Bug D’Art Studio adalah saluran yang paling dekat dengan struktur teks aslinya, karena memperkenalkan variasi dengan tetap mempertahankan inti cerita. Meskipun terjadi perubahan struktural, nilai-nilai budaya loyalitas, tanggung jawab, dan identitas lokal tetap ada. Nilai-nilai ini disampaikan dengan cara yang lebih mudah dipahami oleh anak-anak. Oleh karena itu, adaptasi layar dalam animasi YouTube dapat dipahami sebagai proses negosiasi naratif dan budaya yang memungkinkan cerita rakyat tetap hidup dalam sastra anak digital.